Perception of Cyberbullying in Adolescence: A Brief Evaluation Among Italian Students - Saladino, Valeria; Eleuteri, Stefano; Verrastro, Valeria; Petruccelli, Filippo (Frontiers in Psychology, 2020)
Cyberbullying is associated to the expansion of digital devices and the Internet. In Italy and in other European and non-European countries the phenomenon is growing. Young people who suffer from cyberbullying develop psychopathological symptoms of anxiety, depression and social phobia that can lead to extreme acts, such as suicide. The pressure, the sense of isolation and helplessness experienced by cyber-victims also affect their family and the school context. Cyberbullying is acted through digital tools, it is often anonymous, and aims to destroy and psychologically humiliate the victim. There are various forms of cyberbullying that involve different reactions and consequences. However, few studies focused on the adolescents’ perception of cyberbullying. In fact, youths often engage in aggressive behaviors ignoring the feelings and reactions of the victims. Based on these considerations, our article aims to provide a general overview of the spread of the phenomenon and to understand the various types of cyberbullying and its consequences on victims. We will also illustrate a brief evaluation conducted in Italian schools investigating the perception of cyberbullying in a sample of 600 Italian adolescents (11-14 years old). Our work aims to investigate the cognition and the personal perception of youths about cyberbullying and its consequences and to promote educational interventions in school context and outside it.